SUHU NETRAL DAN RENTANG SUHU NYAMAN MANUSIA INDONESIA (Studi Kasus Penelitian Pada Bangunan Kantor Di Makassar) - M. Husni Kotta (Metropilar - Jurnal Ilmiah Fakultas Teknik, 2008)
The current standart for thermal in Indonesia is based on  ASHRAE 55-1999 (the American Standard) This standard recommends a neural temperature of 240 C, with the range of comfort between 22,50 C and 26 0C to result a thermal comfort. Study done by the author in Makassar in 2005, in which some 596 office workers from seven  multi-storey office buildings were participated in this study,showedthat these  values  were fairly to low to the average requirement of the Indonesian workers   who were(about 95% of the sample population) still comfortable within the range temperature of 24,9 0C to 28,50 C in terms of air temperature(To)or 25,10 C to 27,90 C in terms of operative temperature(To). The Lower the values of the standard would result to the higher energy consumption in the air condioned Buiding. the frinciple comparative in value divus and global there date value the had processing are kuality conditions in conditions date sky. The long day,are 97 day Clear Sky (30%), in 179 day Intermediate sky  (56%) and 44 day Overcast sky  (14%) Keywords: air temperature, operative temperature, neutral (comfort) temperature, thermal sensation, illumination, radiation.